Pengaruh Latar Belakang Pendidikan Dan Usia Jemaah Calon Haji Dalam Memahami Materi Bimbingan Manasik Ibadah Haji: (Studi Kasus Di Kabupaten Lamongan dan Kota Kendari) - Rif’ah, Sifwatir; Badrut Tamam, Ahmad (MADINAH, 2019)
Hajj is a form of worship in a very detailed manner that requires the prospective congregation to study it seriously. The report of the Indonesian Hajj Supervisory Commission in 2018 states that 39.32% of pilgrims do not understand the terms, pillars, sunnah and prohibitions of Hajj. This problem needs the attention of the hajj organizers. This study is in order to determine how much influence the educational background and age of the pilgrims' age in the level of understanding absorption in the guidance of the Hajj rituals held by the government. All independent variables, namely educational background and age of the pilgrims, have a significant effect simultaneously on the understanding of the Hajj ritual guidance material.